Os periódicos franceses na imprensa carioca oitocentista Uma leitura dos editoriais de primeira edição - Peruchi, Amanda (Universidade Federal de São Paulo - UNIFESP, 2018)
Abstract The royal family landing in Rio de Janeiro in 1808 began a significant process of modernization, driven by the need to redefine its urban setting, by institutionalizing the press and by the presence of foreigners of different nationalities - especially after the Treaty of Peace (1814) which restablished the french relantionship with European countries and their respective colonies. At this point, many were the French who came to Rio de Janeiro and settled their different businesses through the streets of the imperial capital, especially typographical businesses, during the nineteenth century. As owners of printing houses and/or bookstores, such Frenchmen actively participated in the printing world on the Imperial Rio de Janeiro, as they engaged in the production and sale of books, pamphlets and periodicals, written in Portuguese and in French. Thus, the main objective of this article is to make known a little of these French periodicals produced in the court, between the years of 1827 and 1896, that were part of the Carioca press of the Eightieth, for which we will list, from the texts of the editorials of their first editions, the publishers’ arguments to produce these printed matter, and the main subjects that these editors claimed they wanted to address in their respective journals.

Resumo O desembarque da família real ao Rio de Janeiro, em 1808, deu início a significativo processo de modernização da cidade, impulsionado, entre outras razões, pela necessidade de redefinir seu cenário urbano, pela institucionalização da imprensa e pela presença de estrangeiros de diversas nacionalidades - especialmente após o Tratado de Paz de 1814 que, entre outras medidas, retomou as relações da França com os países europeus e suas respectivas colônias. Neste palco, muitos foram os franceses que vieram para o Rio de Janeiro e instalaram seus diferentes negócios pelas ruas da capital imperial, sobretudo os negócios tipográficos. Seja como proprietários de casas de impressão e/ou livrarias, tais franceses participaram ativamente do mundo dos impressos no Rio imperial, uma vez que se envolveram com a produção e venda de livros, folhetos, panfletos e periódicos, esses, escritos em língua portuguesa e em língua francesa. Deste modo, o principal objetivo deste artigo é dar a conhecer um pouco desses periódicos franceses produzidos na corte, entre os anos de 1827 e 1896, que fizeram parte da imprensa carioca do Oitocentos, para o que listaremos, a partir dos textos dos editoriais de suas primeiras edições, os argumentos dos editores para a produção desses impressos e os principais assuntos que estes editores afirmaram querer abordar em seus respectivos periódicos.
The French newspapers in the carioca press of the Eighteenth A reading of first edition editorials
Keywords: press in Rio; French newspapers; XIX century; imprensa carioca; periódicos franceses; século XIX